2022
DOI: 10.1186/s12902-022-00938-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of diabetes distress among adults with type 2 diabetes mellitus: a facility-based cross-sectional study of Bangladesh

Abstract: Introduction Diabetes distress (DD) is common and has considerable impacts on diabetes management. Unfortunately, DD is less discussed and frequently underestimated. This study evaluated the prevalence and predictors of DD in adults with type 2 diabetes mellitus (T2DM). Methods A cross-sectional study was conducted at several specialized endocrinology outpatient clinics in Bangladesh from July 2019 to June 2020; 259 adults with T2DM participated. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 26 publications
9
34
0
Order By: Relevance
“…In the current study, diabetes duration, complications and treatment regimen were all associated with increased risks for comorbid DD, depression, and anxiety symptoms, which is consistent with previous studies (53,55,58). However, it is difficult to interpret potential risk factors for mental health disorders in T2DM as these factors often coexist and interact with each other.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the current study, diabetes duration, complications and treatment regimen were all associated with increased risks for comorbid DD, depression, and anxiety symptoms, which is consistent with previous studies (53,55,58). However, it is difficult to interpret potential risk factors for mental health disorders in T2DM as these factors often coexist and interact with each other.…”
Section: Discussionsupporting
confidence: 86%
“…Complex interactions between DM and social as well as cultural dynamics are likely to affect the way patients experience illness and health (50). Our study did not find an association between gender and higher risk for developing DD which is consistent with Kamrul-Hasan et al findings (53). However, bivariant analysis showed that females had higher risk for developing depression and anxiety although that was not confirmed with subsequent multivariant analysis.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In contrast to the aforementioned decreasing amputation rates, a study on national population data from Singapore revealed increasing diabetes‐associated annual amputation rates within the observation period from 2008 to 2017 44 . The vast global and ethnic differences concerning risk for DM related to lower extremity complications and amputations were recently shown by different studies 45,46 . Data from Germany revealed controversial results regarding outcome and amputation of diabetic PAD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 44 The vast global and ethnic differences concerning risk for DM related to lower extremity complications and amputations were recently shown by different studies. 45 , 46 Data from Germany revealed controversial results regarding outcome and amputation of diabetic PAD patients. German nationwide data comprising the years 2005, 2007 and 2009 demonstrated declining rates of major and inclining minor amputations in PAD patients.…”
Section: Discussionmentioning
confidence: 99%